Transforming business education for a sustainable future stories from pioneers - Fritz, Morgane; Irwin, Linda; Weichert, James; Rimanoczy, Isabel 1956- (Abingdon, Oxon New York, NY Routledge, 2024)
"As the impact of climate change becomes more evident and dire, business leaders, educators, students, and academic leaders are deciding what they need to learn and do to survive and thrive in a new and dramatically different environment. This book clearly sets out how to transform business education and integrate sustainability into curriculum and a wider academic culture. While some universities around the globe are still teaching business practices that have contributed to several crises, pioneering educators and higher education institutions are researching, developing, and implementing programs to transform business education and practices. With stories from 26 administrators, researchers, and faculty across the globe, this book inspires business educators with innovative tools and creative solutions to address challenges in the business world and society. These pioneers are helping students and business ventures change the way they conduct business to survive and thrive in a fast-changing global environment. Their unique and personal journeys offer tools, models, lessons-learned, and inspiration for change. The book will both inspire and steer faculty members, administrators, students, and alumni to transform business education for a sustainable future"--
Includes bibliographical references and index.
Keywords: Business education; Executives -- Training of